Pengaruh Perawatan Metode Kangguru Terhadap Peningkatan Berat Badan Pada Bayi BBLR Di Ruang Perinatologi RSUD Kota Tanjungpinang - Indah Purnama S; Elvi Murniasih; Tiora Silalahi (An-Najat, 2023)
Neonates are a transition period from intrauterine to extrauterine life that live with limitations according to the gradual maturity of body organ function. During this period, neonates can be at high risk of experiencing health problems, one of which is low birth weight (LBW). Phenomenon in the Perinatology Room at Tanjungpinang City Regional Hospital, by observing 3 mothers who had babies with low birth weight using the kangaroo method, it was found that 1 person experienced weight gain after kangaroo treatment for 5 days. Meanwhile, 2 other people did not experience an increase. This is due to the mother's or family's lack of knowledge regarding kangaroo method care (PMK). In 2021, neonatal deaths in the Riau Islands Province were still dominated by LBW causes at 42% (102 cases) and data from the perinatology room at the Tanjungpinang City Regional Hospital in 2022 and January-March 2023 saw 46 babies born with LBW. Pre-experimental research method. The research design uses a one group pre test-posttest design approach without control group. The sample numbered 30. It was concluded that there was an influence of the kangaroo method of care on increasing body weight in LBW babies. Suggestions for hospitals for this therapy can be considered as the first treatment for LBW newborns to increase the baby's weight.